1986
DOI: 10.1152/ajpendo.1986.251.3.e334
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response curves of effects of insulin on leucine kinetics in humans

Abstract: To determine the effects of physiological and pharmacological insulin concentrations on leucine-carbon kinetics in vivo, eight postabsorptive normal volunteers were infused with L-[4,5-3H]leucine and alpha-[1-14C]ketoisocaproate (KIC). Insulin concentrations were sequentially raised from 8 +/- 1 to 43 +/- 6 and 101 +/- 14 and to 1,487 +/- 190 microU/ml, while maintaining euglycemia with adequate glucose infusions. At the end of each 140-min insulin-infusion period, steady-state estimates of leucine and KIC rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 9 publications
10
69
0
Order By: Relevance
“…In normal subjects, insulin suppresses proteolysis in a dosedependent manner (17,23). Castellino et al (9) and Tessari et al (17) found that insulin also suppresses leucine oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal subjects, insulin suppresses proteolysis in a dosedependent manner (17,23). Castellino et al (9) and Tessari et al (17) found that insulin also suppresses leucine oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Total infusion time was 540 min. Tessari et al (17) used similar successive short infusion protocol to study the dose-response relationship of insulin on leucine kinetics in humans. Solutions were infused through a venous catheter in one forearm, and blood samples were collected from a vein in the contralateral arm.…”
Section: Methodsmentioning
confidence: 99%
“…Human studies employing recombinant IGF1 provide the strongest evidence that circulating IGF1 is anabolic. IGF1 enhances protein anabolism by reducing the rate of proteolysis, an action similar to that of insulin (Fukagawa et al 1985, Tessari et al 1986, Jacob et al 1989. When IGF1 is infused in rats, it leads to a reduction in protein breakdown without any change in protein synthesis (Jacob et al 1989).…”
Section: Gh Effects On Protein Metabolismmentioning
confidence: 99%
“…Although the conventional clamp achieves hyperinsulinemia within the postprandial range, it does not replicate postmeal circulating metabolite concentrations. Indeed, it generates hypoaminoacidemia by insulin inhibition of protein catabolism, thereby preventing the testing of insulin sensitivity of protein anabolism by decreasing amino acid (AA) availability (6,38,46). Since insulin stimulation of protein synthesis and inhibition of proteolysis are unambiguously established in vitro, and abnormal protein metabolism occurs in both type 1 (45) and type 2 diabetes (17,19) we have previously used an hyperinsulinemic, euglycemic, isoaminoacidemic clamp (8) to explore whole body protein turnover.…”
mentioning
confidence: 99%